Clinico-epidemiological study of respiratory distress in newborn and associated risk factors - Sodawat, Rishi; Garg, Pukhraj; Singh, Chaturbhuj; Sharma, Priyanka (International Journal of Contemporary Pediatrics, 2018)
Background: Respiratory distress (RD) is one of the most common causes of admission in neonatal intensive care unit (NICU) for a variety of pulmonary and non-pulmonary disorders. This study has been undertaken to evaluate prevalence of the known causes and risk factors associated with development of respiratory distress in neonates and finally to assess the clinical correlation with blood investigations, X-RAY, ECG, ABG and 2D ECHO. Methods: The present study was conducted in the department of Pediatrics at JLNMC Ajmer between February 2017 – February 2018, over a period of 12 months. It is a prospective case study. Results: Out of 600 newborns admitted with respiratory distress, Transient Tachypnea of Newborn (TTN) was found to be the most common cause (n = 196, 32.6%) followed by HMD (n = 145, 24.1%). Conclusions: Transient tachypnea of newborn is the most common cause among new-borns with respiratory distress. Majority of newborns develop severe distress within 6 hours after birth. In preterm and term babies the major cause of RD is Hyaline membrane disease (HMD) and HIE/CHD (hypoxic enchephalopathy/congenital heart disease) respectively. While in post term babies MAS is major cause of RD. Newborns with low and very low birth weight are more prone for development of severe distress.